Enhanced piezocatalytic hydrogen production of molybdenum disulfide by metal organic framework-derived magnetic NiFe2O4@carbon nanohybrids - Linli Hou; Wenting Zhang; Mang Lu; Huanggen Yang; Limin Liu (Journal of Environmental Chemical Engineering, 2026)

Multi-omics reveals metabolic division of labor in mixed-starter soymilk fermentation - Jiahui Li; Jiahui Yang; Linli Zhang; Tonghao Du; Zhen Peng; Shijin Xiong; Muyan Xiao; Tao Xiong; Mingyong Xie (Food Research International, 2026)

Peri-implantation 6PPD-Q exposure impairs endometrial decidualization and induces pregnancy loss - Wanting Fu; Ziyao Yang; Yi Li; Tianxiao Chen; Qingling Yang; Linli Hu (Journal of Hazardous Materials, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Meta-analysis of Probiotic Interventions in Roux-en-Y Gastric Bypass and Sleeve Gastrectomy: Effect on Cardiovascular Risk Factors - Banghao Xie; Hong Yong; Qi Liu; Linli Hu; Meixue Yang (Probiotics and Antimicrobial Proteins, 2026)

Chinese AgroMeteorological Model CAMM 2.0–3.0: System Framework, Mechanistic Innovations, and Operational Applications - Yuping Ma; Dingrong Wu; Jianying Yang; Youhao E; Qi Wang; Shuang Sun; Linli Sun; Min Xu; Dianchen Han; Yang Li; Yuanda Zhang; Qianchuan Mi; et al. (Journal of Meteorological Research, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

De novo synthesis of tryptanthrin and its derivatives from indole: engineering a sustainable photocatalytic strategy - Ya Zhou; Junrong Zhang; Ya Xiao; Hongwu Liu; Guoqing Wang; Linli Yang; Wujun Jian; Dan Zeng; Xiang Zhou; Song Yang (Molecular Diversity, 2026)

OsTIP1;2 is a key regulator of rice seed germination and stress resilience - Xin Liu; Linli Ben; Siyuan Tang; Yingbo Gao; Xiaoxiang Zhang; Guichun Dong; Juan Zhou; Zefeng Yang; Yong Zhou; R. Glen Uhrig; Jianye Huang; Youli Yao (Plant Science, 2026)

Polystyrene nanoplastics induce ovarian injury by PI3K-Akt pathway-driven macrophage extracellular trap formation - Yingying Chen; Linli Yang; Yuanyuan Li; Lulu Si; Hanlin Fu; Tianjiao Lai; Ruixia Guo (Environmental Pollution, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Natural-product repurposing for novel reactive oxygen species inducer discovery: bactericidal profiling and structure-activity relationship of ellipticine and its analogs - Jingsha Yang; Guoqing Wang; Yi He; Wan Chen; Hongwu Liu; Linli Yang; Dan Zeng; Zhibing Wu; Liwei Liu; W.M.W.W. Kandegama; Zhenbao Luo; Xiang Zhou; et al. (Physiological and Molecular Plant Pathology, 2025)

Time-series NDVI and greenness spectral indices in mid-to-late growth stages enhance maize yield estimation - Dayun Feng; Hongye Yang; Kexin Gao; Xiuliang Jin; Zhenhai Li; Chenwei Nie; Guoqiang Zhang; Liang Fang; Linli Zhou; Huirong Guo; Zhijie Jia; Bo Ming; et al. (Field Crops Research, 2025)

Heterogeneous Rb-Sr isotopes in Chang’e-5/6 soils: implication for geochemical study of extraterrestrial samples - Le Zhang; Guanhong Zhu; Zhiming Chen; Jingyou Chen; Yan-Qiang Zhang; Zexian Cui; Chengyuan Wang; Haiyang Xian; Xianglin Tu; Jintuan Wang; Qing Yang; Ya-Nan Yang; et al. (Science Bulletin, 2025)

Corrigendum to “Development of downscaling technology for land surface temperature: A case study of Shanghai, China” [Urban Climate 61 (2025) 102412] - Shitao Song; Jun Shi; Dongli Fan; Linli Cui; Hequn Yang (Urban Climate, 2025)

Carbon dots modified metallated graphdiyne with enhanced electron transfer and O2 adsorption capacity for efficient H2O2 photoproduction - Honglin Si; Mude Zhu; Zenan Li; Jiaxuan Wang; Jiacheng Li; Linli Xu; Hui Huang; Yang Liu; Wai-Yeung Wong; Zhenhui Kang (Chemical Engineering Journal, 2025)

Development of downscaling technology for land surface temperature: A case study of Shanghai, China - Shitao Song; Jun Shi; Dongli Fan; Linli Cui; Hequn Yang (Urban Climate, 2025)

Transport and action of sesame protein-derived ACE inhibitory peptides ITAPHW and IRPNGL - Tonghao Du; Jiahui Yang; Yuan Qin; Xizhuo Huang; Jiahui Li; Shijin Xiong; Xiaoyan Xu; Linli Zhang; Mingwei Zhao; Huiyu Li; Tao Huang; Tao Xiong; et al. (Food Chemistry, 2025)

Characterization and toxicological effects of microplastics in PM2.5 in background sites of the southern coast of China - Jian Sun; Jiaer Yang; Steven Sai Hang Ho; Zezhi Peng; Xinyi Niu; Linli Qu; Ka Hei Lui; Hai Guo; Kin-Fai Ho (Atmospheric Environment, 2024)

Insight into emission reduction effect of coal and biomass mixed briquette fuel - Kun He; Zhenxing Shen; Yiming Yang; Bin Zhang; Jian Sun; Hongmei Xu; Steven Sai Hang Ho; Linli Qu; Junji Cao (Journal of Cleaner Production, 2024)

Tree species classification improves the estimation of BVOCs from urban greenspace - Xinxin Bao; Weiqi Zhou; Weimin Wang; Yang Yao; Linli Xu (Science of The Total Environment, 2024)

The economic and environmental sustainability of converting Miscanthus to hydrocarbon biofuel by pyrolysis and catalytic hydrotreatment - Yuxiang Ma; Hong Tian; Hua Cheng; Yanni Xuan; Linli Shang; Yang Yang (Biomass and Bioenergy, 2024)

Fusaricidin produced by the rhizobacterium Paenibacillus polymyxa NX20 is involved in the biocontrol of postharvest plant-pathogenic oomycete Phytophthora capsici - Chenjie Yu; Xihao Yang; Xiaoli Liang; Yan Song; Linli Zhu; Shuyue Xing; Yang Yang; Qin Gu; Rainer Borriss; Suomeng Dong; Xuewen Gao; Huijun Wu (Postharvest Biology and Technology, 2023)

OsUGE1 is directly targeted by OsGRF6 to regulate root hair length in rice - Shuaiqi Yang; Nuo Xu; Nana Chen; Jiaxuan Qi; Abdul Salam; Junyu Wu; Yihua Liu; Linli Huang; Bohan Liu; Yinbo Gan (Theoretical and Applied Genetics, 2023)

Effects of DPTQ, a novel positive allosteric modulator of the dopamine D1 receptor, on spontaneous eye blink rate and spatial working memory in the nonhuman primate - Stacy A. Castner; Linli Zhang; Charles R. Yang; Junliang Hao; Jeffrey W. Cramer; Xushan Wang; Robert F. Bruns; Hugh Marston; Kjell A. Svensson; Graham V. Williams (Psychopharmacology, 2023)
Rationale Dopamine (DA) signaling through the D1 receptor has been shown to be integral to multiple aspects of cognition, including the core process of working memory. The discovery of positive allosteric modulators (PAMs) of the D1 receptor has enabled treatment modalities that may have alternative benefits to orthosteric D1 agonists arising from a synergism of action with functional D1 receptor signaling. Objectives To investigate this potential, we have studied the effects of the novel D1 PAM DPTQ on a spatial delayed response working memory task in the rhesus monkey. Initial studies indicated that DPTQ binds to primate D1R with high affinity and selectivity and elevates spontaneous eye blink rate in rhesus monkeys in a dose-dependent manner consistent with plasma ligand exposures and central D1activation. Results Based on those results, DPTQ was tested at 2.5 mg/kg IM in the working memory task. No acute effect was observed 1 h after dosing, but performance was impaired 48 h later. Remarkably, this deficit was immediately followed by a significant enhancement in cognition over the next 3 days. In a second experiment in which DPTQ was administered on days 1 and 5, the early impairment was smaller and did not reach statistical significance, but statistically significant enhancement of performance was observed over the following week. Lower doses of 0.1 and 1.0 mg/kg were also capable of producing this protracted enhancement without inducing any transient impairment. Conclusions DPTQ exemplifies a class of D1PAMs that may be capable of providing long-term improvements in working memory.

Dissimilatory manganese reduction facilitates synergistic cooperation of hydrolysis, acidogenesis, acetogenesis and methanogenesis via promoting microbial interaction during anaerobic digestion of waste activated sludge - Linli Wang; Yangyang Li; Xuesong Yi; Fei Yang; Dexin Wang; Hongjun Han (Environmental Research, 2023)

Enhancing thermostability and activity of sucrose phosphorylase for high-level production of 2-O-α-d-glucosylglycerol - Linli Yang; Lukasz Peplowski; Yujuan Shen; Haiquan Yang; Xianzhong Chen; Wei Shen; Yuanyuan Xia (Systems Microbiology and Biomanufacturing, 2022)